EUS-guided FNA for biliary disease as first-line modality to obtain histological evidence. (May 2016) - Onda, Saori; Ogura, Takeshi; Kurisu, Yoshitaka; Masuda, Daisuke; Sano, Tatsushi; Takagi, Wataru; Fukunishi, Shinya; Higuchi, Kazuhide
Background: Few reports have described endoscopic ultrasound (EUS)-guided fine needle aspiration (FNA) for biliary lesions. In addition, adverse events were not completely examined in previous reports, due to the inclusion of cases in which biliary stents had already been placed. The present study aimed to investigate the diagnostic yield and adverse events of EUS-FNA for biliary lesions as the first-line diagnostic modality for consecutive prospectively registered patients. Methods: Inclusion criteria were as follows: (1) patients with suspected cholangiocarcinoma (CCA) based on computed tomography or other imaging modalities; (2) patients who had not previously undergone endoscopic retrograde cholangiopancreatography or EUS-FNA; (3) absence of surgically altered anatomy, such as Roux-en-Y anastomosis or duodenal obstruction caused by tumor invasion, through which an endoscope could not pass; and (4) provision of written informed consent to all procedures associated with the study. Results: A total of 47 consecutive patients with suspected CCA were registered to this study. Sensitivity and accuracy were 89% and 87%, respectively. On multivariate analysis, puncture site was the only factor associated with reduced diagnostic yield (hazard ration, 6.879; 95% confidence interval, 1.172–40.374; P = 0.033). Remarkably, no adverse events such as bleeding or bile leakage were associated with EUS-FNA in any of the 47 patients. Conclusions: Our results suggest that EUS-FNA can be safely performed for biliary disease without biliary stenting. Furthermore, this procedure may warrant use as the first-line diagnostic method, although our results need to be validated in future prospective studies.